Peptide Self-Assembly Controlled Photoligation of Polymers - Richardson, Bailey J.; Zhang, Chao; Rauthe, Pascal; Unterreiner, Andreas-Neil; Golberg, Dmitri V.; Poad, Berwyck L. J.; Frisch, Hendrik (Journal of the American Chemical Society, 2023)
Highly efficient chemical ligations that operate in water under mild conditions are the foundation of bioorthogonal chemistry. However, the toolbox of suitable reactions is limited. Conventional approaches to expand this toolbox aim at altering the inherent reactivity of functional groups to design new reactions that meet the required benchmarks. Inspired by controlled reaction environments that enzymes provide, we report a fundamentally different approach that makes inefficient reactions highly efficient within defined local environments. Contrasting enzymatically catalyzed reactions, the reactivity controlling self-assembled environment is brought about by the ligation targets themselvesavoiding the use of a catalyst. Targeting [2 + 2] photocycloadditions, which are inefficient at low concentrations and readily quenched by oxygen, short β-sheet encoded peptide sequences are inserted between a hydrophobic photoreactive styrylpyrene unit and a hydrophilic polymer. In water, electrostatic repulsion of deprotonated amino acid residues governs the formation of small self-assembled structures, which enable a highly efficient photoligation of the polymer, reaching ∼90% ligation within 2 min (0.034 mM). Upon protonation at low pH, the self-assembly changes into 1D fibers, altering photophysical properties and shutting down the photocycloaddition reaction. Using the reversible morphology change, it is possible to switch the photoligation “ON” or “OFF” under constant irradiation simply by varying the pH. Importantly, in dimethylformamide, the photoligation reaction did not occur even at 10-fold higher concentrations (0.34 mM). The self-assembly into a specific architecture, encoded into the polymer ligation target, enables a highly efficient ligation that overcomes the concentration limitations and high oxygen sensitivity of [2 + 2] photocycloadditions.